MORPHOLOGICAL DIFFICULTIES IN AN ANATOMICAL PATTERN OF THE CRYSTALS - V.A. Popov (Минералогия)
The study of minerals with modern electron microscopes requires the solution of anatomical problems of the crystals. To obtain consistent spectroscopic data from different instruments, it is necessary to point the microprobe directly to the same element of the crystal anatomy. This is difficult to do unknown details of an anatomical pattern. The article provides the examples of complex arrangement of elements of crystal anatomy of different minerals to accumulate ontogenetic information for the formulation of the postulates.